PEDAGOGICAL AND PSYCHOLOGICAL COMPETENCE OF THE TEACHER (ResearchJet Journal of Analysis and Inventions, 2021)
Focusing on the new socio-economic conditions that have emerged in our country, changes are taking place in the education system, the main task of which is to focus on the personality of the student. The modern school student needs not only information, but also methods and methods of obtaining it. The effectiveness of a student's learning is influenced by the professional competence of the teacher. The need to increase the level of professionalism of educational workers, and the development of their psychological competence is quite an urgent problem.